Scientific and technical aspects of creating spent nuclear fuel shipping and storage equipment - I. R. Shegelman; A. V. Romanov; A. S. Vasiliev; P. O. Shchukin (Ядерна фізика та енергетика)
Details of advanced capacity shipping packaging set development which allows shipping and storage of heat-producing spent fuel assemblies for pressurized water reactor VVER-1000 type are considered. Analogs and achieved advantages of TUK-146 construction are mentioned.